Comparative analyses of serological biomarkers and disease characteristics between elderly-onset and younger-onset rheumatoid arthritis - Rajalingham Sakthiswary,; Syahrul Sazliyana S,; Abdul Wahab A,; Mahadzir H, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
The onset of rheumatoid arthritis (RA) may occur any time after the age of 16 years. The purpose of this study was to compare the clinical and serological differences between elderly onset RA (EORA); which is begins at the age of 60 and above, with younger onset RA (YORA). A total of 69 EORA and 82 YORA female patients were enrolled in this study. Data on medications, disease duration, age at onset, disease activity at onset and laboratory parameters were collected by reviewing the medical records. All patients had their blood samples taken for serum anti-cyclic citrulinated peptide (anti-CCP), IgA rheumatoid factor (RF), IgM RF and IgG RF. Besides, the subjects were assessed for their radiographic joint damage based on Modified Sharp Score (MSS) and functional disability based on the Health Assessment Questionnaire-disability Index (HAQ-DI) scores. Despite comparable disease duration and frequency of seropositivity, the YORA group had significantly higher disease activity at onset of the disease (p=0.009). In keeping with this finding, the YORA group had more severe joint damage based on radiographic assessment (MSS scores of 17.49+19.04 versus 10.04+12.79). The YORA group had significantly higher levels of IgA RF and anti-CCP with p-values of 0.035 and 0.002, respectively. Our findings suggest that YORA is associated with more severe disease, worse radiographic joint damage and higher levels of anti-CCP and IgA RF.